Influence of Islamic work ethics on organizational commitment amongst construction professionals - Nur Syamimi , Baharudin; Mohyin, Nur Affah (2013)
Islam urges all Muslims to perform well at work by giving full commitment to it. Religious behaviour plays a great influence in actual life which is beneficial to social and also to organizational development. This paper reviews the literatures on commitment in construction industry. The paper also explores the topics from Islamic perspectives particularly the influence of Islamic work ethics on commitment. It also highlights the importance of Islamic ideology on organizational commitment towards the organizations where the construction professionals work. The reviews discover that positive work values of commitment to perfection in task performance, to one’s welfare and to the welfare of others, can be extracted from Islamic values. These Islamic values such as justice and love, selflessness, faith in God and fear of God can personify the positive commitment at work. It is apparent that the application of Ihsan plays an important role in pursuing the values and placing positive commitment in individuals who practise them. The findings conclude that by showing full commitment to work, the employees can improve their job performance and improve productivity and also efficiency of an organization.